Monitoring serotonin signaling on a subsecond time scale - Dankoski, Elyse C.; Wightman, R. M. (Frontiers in Integrative Neuroscience, 2013)
Serotonin modulates a variety of processes throughout the brain, but it is perhaps best known for its involvement in the etiology and treatment of depressive disorders. Microdialysis studies have provided a clear picture of how ambient serotonin levels fluctuate with regard to behavioral states and pharmacological manipulation, and anatomical and electrophysiological studies describe the location and activity of serotonin and its targets. However, few techniques combine the temporal resolution, spatial precision, and chemical selectivity to directly evaluate serotonin release and uptake. Fast-scan cyclic voltammetry (FSCV) is an electrochemical method that can detect minute changes in neurotransmitter concentration on the same temporal and spatial dimensions as extrasynaptic neurotransmission. Subsecond measurements both in vivo and in brain slice preparations enable us to tease apart the processes of release and uptake. These studies have particularly highlighted the significance of regulatory mechanisms to proper functioning of the serotonin system. This article will review the findings of FSCV investigations of serotonergic neurotransmission and discuss this technique’s potential in future studies of the serotonin system.